Power ahead: Meeting Ethiopia's energy needs under a changing climate - Paul Block; Kenneth Strzepek (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Ethiopia is powering ahead with an ambitious energy development strategy, highly reliant on abundant hydropower potential. A changing climate, including uncertain water supply, however, may pose a salient challenge to meeting expected targets. Bridging the modeling gaps between climate, energy, and economics, and effectively transforming climate changes into economic measures, is an emerging inter-disciplinary field as nations attempt to position themselves for an uncertain future. Such a framework is adopted here to assess energy production and adaptation costs for four climate change scenarios over 2010 - 49. Scenarios that favor a drying trend country-wide may lead to losses of 130 - 200 terawatt hours over the 40-year period, translating to adaptation costs of US 2 - 4 billion, compared to a no climate change scenario. Even given these potential losses, energy development utilizing hydropower appears economically reasonable from this deterministic, sector-independent evaluation. This development is desperately needed, independent of future climate change trends, with the hope of appreciably reducing vulnerability to variability.
Keywords: Q25; Q43; Q54; 330; Ethiopia; energy development; hydropower; climate change; economics